Shutter Island - Haley, Jackie Earle, 1961-; DiCaprio, Leonardo; Ruffalo, Mark.; Sydow, Max von, 1929-; Williams, Michelle, 1980-; Kingsley, Ben, 1943-; Scorsese, Martin; Lehane, Dennis; Kalogridis, Laeta; Medavoy, Mike.; Messer, Arnold W.; Fischer, Bradley J.; et al. (Hollywood, Calif. : Paramount Home Entertainment, 2010)
When U.S. Marshall Teddy Daniels arrives at the asylum for the criminally insane on Shutter Island, what starts as a routine investigation quickly takes a sinister turn. As the investigation unfolds and Daniels uncovers more shocking and terrifying truths about the island, he also learns there are some places that never let you go.
Based on the novel by Dennis Lehane.
Originally produced as a motion picture in 2010.
Production designer, Dante Ferretti ; edited by Thelma Schoonmaker ; costume designer, Sandy Powell ; visual effects supervisor, Rob Legato ; music supervision by Robbie Robertson ; co-producers, Joseph Reidy, Emma Tillinger, Amy Herman.
Jackie Earle Haley, Leonardo Dicaprio, Mark Ruffalo, Max Von Sydow, Michelle Williams, Ben Kingsley.
MPAA Rating: R; for disturbing violent content, language and some nudity.
DVD; region 1, NTSC; widescreen (16:9, enhanced) presentation; Dolby digital 5.1 surround.
Keywords: Lehane, Dennis -- Film adaptations; United States. -- Marshals Service -- Drama; Asylums -- Drama; Missing persons -- Investigation -- Drama; Islands -- Drama; Psychiatric hospital patients -- Drama; French language materials; Spanish language materials; Feature films; Thrillers (Motion pictures); Film adaptations; Video recordings for the hearing impaired; Video recordings for the hearing impaired